Oxygen-vacancy-enhanced piezo-photocatalytic performance of AgNbO3. (1st January 2022) - Li, Li; Ma, Yanran; Chen, Gaifang; Wang, Jingsong; Wang, Chunchang
Abstract: Piezo-photocatalysis (implement by ultrasound vibration and UV-vis light irradiation), a new-emerging strategy, can suppress the rapid recombination of electrons and holes to enhance the catalytic performance. The modulation of interface structures (e.g., the introduction of oxygen vacancies, OVs) plays a significant role in the charge-transfer and the catalytic activity. In this paper, the AgNbO3 (ANO) powder was prepared by a facile hydrothermal method. Based on this, we introduce OVs into ANO successfully by annealing in N2 (ANO-N2 ). The ANO-N2 with OVs exhibits much better piezo-photocatalytic activity for degradation of Rhodamine B (RhB) than the ANO. The result found that OVs can narrow the band gap and improve the UV-vis light absorption, and most importantly, promote the separation of electron hole pairs under electric field to enhance the piezo-photocatalytic performance. The work thus supplies an in-depth understanding of the mechanism between OVs and piezo-photocatalytic performance. Graphical abstract: Image, graphical abstract